The Bounty of Texas - Abernethy, Francis Edward; Project Muse. (College Station : Texas A & M University Press [distributor], 1990)
Annotation A collection of eighteen pieces celebrating the bounty of Texas, complete with photographs featuring some of the bounty in deceased form. Consists of reminiscences, humor, and homage to some of the converging cultures that make up Texas--general nostalgia. Annotation copyrighted by Book News, Inc., Portland, OR.
Description based on print version record.
Keywords: Manners and customs; Folklore; Folklore -- Texas; Texas; Texas -- Social life and customs; Electronic books